2001
DOI: 10.4049/jimmunol.166.4.2712
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Overexpression Predisposes to Anaphylaxis Following Antigen Sensitization

Abstract: Anaphylaxis represents an extreme form of allergic reaction. This acute-phase component of allergy and asthma is triggered by allergen-induced degranulation of mast cells following the cross-linking of cell surface-bound, allergen-specific IgE, resulting in the liberation of inflammatory mediators and the development of bronchoconstriction. We used IL-13 transgenic mice to investigate the role of this Th2 cell-derived cytokine in the onset of allergic disease. Strikingly, IL-13-transgenic mice were highly pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 29 publications
(42 reference statements)
4
52
2
1
Order By: Relevance
“…Conversely, reduced levels of IgE have been reported in IL-13-deficient mice, suggesting that IgE levels are responsive to both an increase and a decrease in the expression of IL-13 (27). Moreover, the role of IL-13 in the development of anaphylactic symptoms is well-documented (28,29). Sensitization of mice in which IL-13 is overexpressed in lymphoid cells results in the enhanced production of FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, reduced levels of IgE have been reported in IL-13-deficient mice, suggesting that IgE levels are responsive to both an increase and a decrease in the expression of IL-13 (27). Moreover, the role of IL-13 in the development of anaphylactic symptoms is well-documented (28,29). Sensitization of mice in which IL-13 is overexpressed in lymphoid cells results in the enhanced production of FIGURE 8.…”
Section: Discussionmentioning
confidence: 99%
“…Individual serum samples (five mice per group) were measured and are expressed as the geometric means Ϯ SEM. Ag-specific IgE and the rapid induction of fatal anaphylaxis (28). In asthma models, IL-13 has also been shown to be particularly important for the induction of the bronchial constriction and the smooth muscle cell contraction that characterizes the airway symptoms of an allergic response (30).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, despite IL-13 transgenic mice being predisposed to anaphylaxis caused by schistosome eggs (10), these mice had no anaphylactic symptoms during acute or chronic S. mansoni infection. Therefore, in this study we evaluated whether schistosome infection renders mice less susceptible to anaphylaxis using an experimental murine model of systemic anaphylaxis.…”
Section: Helminth Infection Protects Mice From Anaphylaxis Via Il-10-mentioning
confidence: 90%
“…We have previously shown that mice that overexpress IL-13 develop anaphylaxis after sensitization and re-exposure to Schistosoma mansoni eggs (10). Anaphylaxis is an acute, life-threatening, allergic reaction that can cause fatalities after exposure to allergenic Ags in sensitized atopic individuals.…”
Section: Helminth Infection Protects Mice From Anaphylaxis Via Il-10-mentioning
confidence: 99%
See 1 more Smart Citation